2003
DOI: 10.1111/j.1752-1688.2003.tb03679.x
|View full text |Cite
|
Sign up to set email alerts
|

RAINFALL POINT INTENSITIES IN AN AIR MASS THUNDERSTORM ENVIRONMENT: WALNUT GULCH, ARIZONA1

Abstract: Point rainfall intensities for a given return period are often used to formulate design storms for rainfall/runoff models to simulate design floods. These design floods are in turn used to design bridges, culverts, and a variety of drainage and flood control structures. The projected rapid growth in the southwestern United States will require very substantial monetary investments in drainage infrastructure. Accurate estimates of point rainfall intensities are critical to ensure both safe designs while not wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…0.3 mm) likely resulting from the spatial averaging of highly spatially heterogeneous rainfall. The rainfall intensities that we report here are comparable to those reported by Mendez et al (2003) for a 60 min rainfall event, which was the approximate mean duration of rainfall at our sites. Because rainfall characteristics were not significantly different between years, we pooled runoff and rainfall observations made during runoff monitoring to examine spatial controls on runoff quantity and quality.…”
Section: Monsoonal Rainfall and Hydrologic Responsessupporting
confidence: 88%
“…0.3 mm) likely resulting from the spatial averaging of highly spatially heterogeneous rainfall. The rainfall intensities that we report here are comparable to those reported by Mendez et al (2003) for a 60 min rainfall event, which was the approximate mean duration of rainfall at our sites. Because rainfall characteristics were not significantly different between years, we pooled runoff and rainfall observations made during runoff monitoring to examine spatial controls on runoff quantity and quality.…”
Section: Monsoonal Rainfall and Hydrologic Responsessupporting
confidence: 88%
“…Large portions of these areas are experiencing accelerated erosion as a result of cumulative impacts of past land management (e.g., overgrazing), drought, and fire (Allen and Breshears, 1998; Davenport et al, 1998; Wilson et al, 2001) or recent land development. For all of these cases, accurate estimates of runoff and sediment yield are important for understanding ecosystem response and cost‐effective planning and design (Mendez et al, 2003). Furthermore, as climate change progresses, more extreme precipitation events are expected (IPCC, 2001), leading to increased erosivity (Nearing, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fulton et al [1998] reported values ranging between 75 and 150 mm/h. Mendez et al [2003] analyzed maximum gauge intensities at different durations and frequencies for summer thunderstorms over Walnut Gulch. They found that the maximum 5‐min intensities (i.e., at the radar data time step) frequently exceeded 103.8 mm/h, and sometimes were near 250 mm/h.…”
Section: Methodology and Analytic Toolsmentioning
confidence: 99%
“…Using radar data, Morin et al [2006] modeled rain cells as circular Gaussian elements with a maximum intensity and a decay factor: these can give theoretical maximum pixel‐scale intensities greater than 103.8 mm/h. From the latter two studies, and because flash flood forecasting mainly deals with intense rainfall over short return periods, we raised the hail threshold to a reasonable 146.3 mm/h, which has been estimated as the mean of the maximum 5‐min gauge intensities for a 10‐year return period [ Mendez et al , 2003]. Note that the actual WG11 peak storm intensities are rarely close to, and are mostly less than, this new value (Table 2).…”
Section: Methodology and Analytic Toolsmentioning
confidence: 99%